Effect of Late Nitrogen Fertilization on Grain Yield and Grain Filling in Corn - J. A. Fernandez; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2019)
For decades, yield improvement in corn has been accompanied by an increase in plant nitrogen (N) uptake. Modern hybrids are absorbing more N during reproductive stages, while delaying N remobilization to the grain for later in the growing season. To evaluate the effect of late-season N applications in distinct corn genotypes, grain yield and grain filling parameters were evaluated in field experiments under early and late N regimes during 2017 and 2018 growing seasons. Hybrids with different release years (3394, 1990s; P1151, 2000s; and P1197, 2016) and contrasting N application scenarios (including a zero-N control) were evaluated at the Kansas State University Ashland Bottoms Research Farm, Manhattan, KS. Results showed that under N stress conditions, the absence of N fertilization in corn significantly reduced yields, by affecting both grain number (GN) and grain weight (GW). Regarding genotypes, a positive trend was found between the year of release of the hybrid and yields, with greater yields for the modern hybrid (i.e., 206 bu/a for P1197). No significant effects were found between N applied at silking or 2 weeks after R1 for the 2017 field study; comparably, no impact of including an additional application at V12 was detected during 2018. In respect to the grain filling process, N fertilization significantly increased the grain filling duration (GFD) and grain filling rate (GFR). Still, evaluations across altered source-sink ratios are needed in order to investigate whether differential responses to late-season N are determined by variations in the availability of assimilate.
Keywords: late nitrogen; grain filling duration; grain filling rate; maize